Friends. The complete eighth season 8 [videorecording (DVD)] - Cox, Courteney. 1964-; Schwimmer, David, 1966-; Aniston, Jennifer; LeBlanc, Matt; Perry, Matthew, 1969-; Kudrow, Lisa; Crane, David, 1957-; Kauffman, Marta, 1956- (Distributed by Warner Home Video, 2010)
Secrets abound in season eight. Who's the father of Rachel's baby? Why can't Phoebe stop thinking about her twin's fiancé? Why can't Joey keep his feelings to himself? And what's behind the locked door of Monica's closet?